The Development of Organizational Social Capital: Attributes of Family Firms* - Arregle, Jean‐Luc; Hitt, Michael A.; Sirmon, David G.; Very, Philippe (Journal of Management Studies, 2007)
abstract We develop and extend social capital theory by exploring the creation of organizational social capital within a highly pervasive, yet often overlooked organizational form: family firms. We argue that family firms are unique in that, although they work as a single entity, at least two forms of social capital coexist: the family's and the firm's. We investigate mechanisms that link a family's social capital to the creation of the family firm's social capital and examine how factors underlying the family's social capital affect this creation. Moreover, we identify contingency dimensions that affect these relationships and the potential risks associated with family social capital. Finally, we suggest these insights are generalizable to several other types of organizations with similar characteristics.